Le péage urbain de Tromsø, l’urbanisme durable à l’épreuve de la périphéricité arctique - Grégoire Tortosa (Cybergeo, 2023)
This article examines the process of setting up the Tromsø city toll, whose very late implementation (2021) raises questions in a country that has made environmental exemplarity a lever for global integration. The article offers a geo-historic reading of this process from a center/periphery prism, discussing the reluctancy of local residents to sustainable land-use planning and their singular bond to car transport. At a time when, elsewhere in Europe, the reconfiguring of centre/periphery relationships is marked by the empowerment of local states in the face of central state supervision, the establishment of the Tromsø city toll is distinctive in that it maintains a strong duality between the southern centrality and its northern periphery. The establishment of the city toll symbolizes the end of the municipality’s State-granted special regime, and reflects Tromsø’s changing status, from the country’s Northern periphery to the arctic projection of Oslo.